Effect of Time Constraint in Exploring Spatial Differences With Balanced Allocation of Performance Factors in a Redrawn Mental Rotation Test - Jeng, Hi-Lian; Lin, Yi-Lung (Frontiers in Education, 2021)
To achieve a comprehensive and unbiased measurement, a mental rotation test (cube form) was redrawn and administered with influential performance factors: time constraint, item type, angular disparity, and rotation/flipping. Item type, angular disparity, and rotation/flipping were systematically balanced into the items of the redrawn Pentomino-MRT, and two time constraint conditions were randomly assigned to 813 Grade 4 to 6 primary students when administering the test. Children of these ages are of investigative interest because they are at crucial stages of spatial ability development and are at an age where associated gender differences emerge. The study demonstrates that spatial gender differences can be detected in Grade 4, are more marked in Grade 5, and become stable in Grade 6. The importance of time constraint is acknowledged in how and at what grade gender differences emerge under the conditions of the performance factors investigated. In particular, the performance of girls reminds us to focus on their spatial ability development if later STEM participation is of concern.